Liberalisierung notwendig. Intercity-Busverkehr in Deutschland. - Maertens, Sven (Deutscher Verkehrs-Verl., 2005)
Im Gegensatz zu den meisten anderen Segmenten des Personenfernverkehrs wird der linienmäßige Intercity-Busverkehr in Deutschland zum Schutz der Bahnen so stark reguliert, dass jeglicher Wettbewerb zwischen Bus und Bahn ausbleibt. In einer Studie des Instituts für Verkehrswissenschaft der Universität Münster wurde untersucht, welche negativen Konsequenzen mit dieser Regulierung verbunden sind und welche Effizienzgewinne im Falle einer Liberalisierung zu erwarten sind. Zudem wurde geprüft, ob und wie Busunternehmen in einem deregulierten Markt für Intercity-Busverkehre Geld verdienen können. Die wichtigsten Ergebnisse werden vorgestellt. difu

To protect the railways from competition, high market entry barriers effectuate that hardly any inter-city buses are running within Germany. From the economic point of view, this regulation is not justifiable because no noteworthy market failure would occur in a deregulated market for inter-city coach traffic. Besides, the regulation has led to mismanagement especially with the Deutsche Bahn AG. A deregulation of this market segment would lead to increased competition in the field of long-distance traffic and cause positive economic effects, as it did in Great Britain in the early 1980s. Today, the German bus companies have lower unit costs per passenger kilometer than their inter-modal competitors but do neither possess any known brands nor sufficient know-how in the fields of marketing, distribution and eCommerce. Thus, for most companies it will be difficult to finance a sustainable entry in a deregulated market for interurban coach services. Most chance of success can be identified for financially sound or experienced foreign firms, especially on routes which are insufficiently served by the railways. difu
Keywords: Öffentlicher Verkehr; ÖPNV; Bus; Busverkehr; Personenfernverkehr; Angebot; Verkehrsunternehmen; Verkehrspolitik; Regulierung; Deregulierung; Fernlinienbus; Verkehrsangebot